2013
DOI: 10.3171/2013.7.jns13462
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhage risk, surgical management, and functional outcome of brainstem cavernous malformations

Abstract: Object The aim of this study was to evaluate the pre- and postoperative rehemorrhage risk, neurological function outcome, and prognostic factors of surgically treated brainstem cavernous malformations (CMs) with long-term follow-up. Methods The authors conducted a retrospective review of the clinical data from 242 patients with brainstem CMs that were surgically treated between 1999 and 2010. Patient charts, imaging findings, and outcomes were examined. Results The study included 242 patients, with a male-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 81 publications
3
60
0
3
Order By: Relevance
“…26 The presence of edema was not necessarily associated with lesion size, and we preferred the speculation of the probable invasiveness of the lesions and the infiltrated normal parenchyma. 35 The hemorrhage risk of a larger lesion size in our study was consistent with that of a prior study. 30 It could be inferred that despite the lowpressure lesions, the intralesional pressure would gradually increase along with the lesion size in the limited volume of the brainstem; if the pressure exceeded a critical point, the lesion could rupture, followed by significant clinical changes.…”
Section: Hemorrhage Risksupporting
confidence: 82%
See 2 more Smart Citations
“…26 The presence of edema was not necessarily associated with lesion size, and we preferred the speculation of the probable invasiveness of the lesions and the infiltrated normal parenchyma. 35 The hemorrhage risk of a larger lesion size in our study was consistent with that of a prior study. 30 It could be inferred that despite the lowpressure lesions, the intralesional pressure would gradually increase along with the lesion size in the limited volume of the brainstem; if the pressure exceeded a critical point, the lesion could rupture, followed by significant clinical changes.…”
Section: Hemorrhage Risksupporting
confidence: 82%
“…Furthermore, studies differed in their hemorrhage definitions, the assumption of a congenital lesion, and neurological function evaluation methods. 1,2,4,14,24,30,35 In our study, we performed a prospective analysis of retrospectively collected data on the cohort of pediatric brainstem CMs with a stringent definition of hemorrhage and found that the annual hemorrhage rate was calculated to be 11.7% per patientyear, that both the presence of perilesional edema and a larger lesion size predicted poorer hemorrhagefree survival and a higher annual hemorrhage rate, and that prospective hemorrhage prevented complete neurological recovery (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, data from various authors imply that an apparent increased hemorrhage risk of brain stem lesions is likely to be caused by a selection bias: Brain stem hemorrhage is more likely to be symptomatic than supratentorial hemorrhage and is therefore more likely to lead to MR imaging. 9,12,18,19 …”
Section: Other Possible Risk Factorsmentioning
confidence: 99%
“…6 Other authors identified prior hemorrhage as an important risk factor for subsequent hemorrhage by comparing hemorrhage rates of CCMs with and without prior hemorrhage. 1,2,5,[7][8][9] According to these studies, hemorrhage rates ranged from 0%-6% and 4.5%-60%, depending on whether prior hemorrhage was or was not present, respectively. 1,2,5,7-9 However, these articles have a lack of comparability because of differing hemorrhage definitions.…”
mentioning
confidence: 99%